A STUDY ON COSMETICS CONSUMPTION AMONG TEENAGE BOYS IN WAYANAD DISTRICT OF KERALA STATE - Abdul Rafeeque (Abhinav National Monthly Refereed Journal of Research in Commerce & Management, 2015)
The study was conducted to investigate the consumption behavior and attitudes towards cosmetics among teenage boys in wayanad district of Kerala state. The research first sought to explore how different variables influence male consumers’ cosmetics purchasing decisions. The secondary research aim was to analyze how metro sexuality was applied in wayanad. Last to seek for identifying what are the key determinants in wayanad young mens’ cosmetics purchasing behaviors. Theoretical framework sought to provide the most relevant theoretical background. In this section, a brief overview of cosmetics markets, the key concepts of the self, the relationship between cosmetics and self-concept, and core theories on consumption behavior have been discussed. This part was mainly based on the review of previous supportive studies. The empirical research was conducted using a quantitative method. The sample was limited to 15-20 aged boys who live in wayanad district of Kerala. Primary data was obtained by the usage of questionnaires, an instrument for collecting information about wayanad men’s consumption behaviors and attitudes towards cosmetics. The result indicated that men’s cosmetics purchasing behaviors are strongly influenced by cultural and personal factors. The main determinants in purchasing behaviors are hygiene functions, features and fragrance of the product, and price-quality relationship. Although the relatively higher average reflected their positive attitudes towards the purchase of cosmetics, they still maintain traditional consumption behaviors. It is crucial for marketers to develop their awareness through employing appropriate marketing communicating tools.